Pengaruh Pembiasaan Salat Dhuha Terhadap Pembentukan Karakter Disiplin Siswa Kelas X di MAN 1 Bogor - Pratama, Aditya Nugraha; Supriadi, Dedi; Nawawi, M. Kholil (Ikatan Dai Indonesia, 2022)
This study aims to determine the effect of the habit of dhuha prayer on the formation of disciplined character of class X students at MAN 1 Bogor. This study uses a quantitative correlational research method. The population used in this study were all class X students at MAN 1 Bogor and took a sample of 65 students using random sampling techniques. Data collection techniques were through observation, questionnaires, and documentation. Based on the results of the calculation of the coefficient of determination, the habit of dhuha prayer contributed 33.1% to the formation of students' disciplined character. Meanwhile, the remaining 66.9% was influenced by other factors outside the variables studied in this study.